Hemostatic Interventions and All-Cause Mortality in Hemodynamically Unstable Pelvic Fractures: A Systematic Review and Meta-Analysis - XuWen Zheng; MaoBing Chen; Yi Zhuang; Jin Xu; Liang Zhao; YongJun Qian; WenMing Shen; Ying Chu (Emergency Medicine International)
Objective. To conduct a systematic review and meta-analysis of the all-cause mortality associated with the most commonly used hemostatic treatments in patients with hemodynamically unstable pelvic fractures. Methods. Up to April 30, 2023, we searched PubMed, Embase, Web of Science, and Cochrane, including the references to qualified papers. A meta-analysis was performed on studies that reported odds ratios (ORs) or the number of events needed to calculate them. The PROSPERO registration number was CRD42023421137. Results. Of the 3452 titles identified in our original search, 29 met our criteria. Extraperitoneal packing (EPP) (OR = 0.626 and 95% CI = 0.413–0.949), external fixation (EF) (OR = 0.649 and 95% CI = 0.518–0.814), and arterial embolism (AE) (OR = 0.459 and 95% CI = 0.291–0.724) were associated with decreased mortality. Resuscitative endovascular balloon occlusion of the aorta (REBOA) (OR = 2.824 and 95% CI = 1.594–5.005) was associated with increased mortality. A random effect model meta-analysis of eight articles showed no difference in mortality between patients with AE and patients with EPP for the initial treatments for controlling blood loss (OR = 0.910 and 95% CI = 0.623–1.328). Conclusion. This meta-analysis collectively suggested EF, AE, or EPP as life-saving procedures for patients with hemodynamically unstable pelvic fractures.